1997
DOI: 10.1074/jbc.272.26.16322
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Neuron Survival during Development by Nerve Growth Factor Binding to the p75 Neurotrophin Receptor

Abstract: Nerve growth factor (NGF) supports the survival and differentiation of distinct populations of peripheral and central neurons. NGF binds to two classes of cell-surface receptors, the protein tyrosine kinase TrkA and the smaller p75 receptor lacking intrinsic catalytic activity. It has been suggested that both receptors are required for NGF high affinity binding, although TrkA appears to be sufficient for transducing most of the biological effects of NGF. Some evidence suggests that p75 could play a modulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 52 publications
2
69
0
Order By: Relevance
“…NTR -TrkA heterodimer model is not supported by structural data (15)(16)(17), and the ligand passing model, although consistent with the finding that a NGF mutant that cannot bind p75 NTR has only low binding affinity (18), is inconsistent with the observation that the extracellular ligand-binding domain of p75 NTR is not required to create high-affinity NGF binding sites (19,20). Therefore, although a heteroreceptor complex may form, and ligand transfer from p75 NTR to TrkA could occur, these mechanisms cannot be the sole basis for the formation of high-affinity binding sites.…”
Section: Nerve Growth Factor (Ngf)mentioning
confidence: 54%
“…NTR -TrkA heterodimer model is not supported by structural data (15)(16)(17), and the ligand passing model, although consistent with the finding that a NGF mutant that cannot bind p75 NTR has only low binding affinity (18), is inconsistent with the observation that the extracellular ligand-binding domain of p75 NTR is not required to create high-affinity NGF binding sites (19,20). Therefore, although a heteroreceptor complex may form, and ligand transfer from p75 NTR to TrkA could occur, these mechanisms cannot be the sole basis for the formation of high-affinity binding sites.…”
Section: Nerve Growth Factor (Ngf)mentioning
confidence: 54%
“…Wild type NGF (binds TrkA and p75 NTR ) serves as an internal control. NGF-KKE mutant (herein termed NGF-C) is a selective TrkA agonist (21,22). The NGF-Delta 9/13 mutant (herein termed NGF-A) is a selective p75 NTR agonist (23).…”
Section: Quantification Of Retinal Structures Using Fourier Domain Opmentioning
confidence: 99%
“…p75 NTR is a membrane glycoprotein that binds all neurotrophins identified to date, but its biological role in mediating the effects of this family of growth factors is not well defined. In addition to forming a high-affinity binding site when coexpressed with trk receptors (Barker and Shooter, 1994;Verdi et al, 1994;Ryden et al, 1997;Bibel et al, 1999), recent evidence has suggested that p75 NTR may also act autonomously to activate signaling cascades involved in apoptosis, mediated either through the generation of ceramide by sphingomyelin hydrolysis or through Traf6 (Dobrowsky et al, 1994;Dobrowsky et al, 1995;Khursigara et al, 1999). Other studies have shown that activation of p75 NTR by nerve growth factor (NGF) causes the translocation of NF-kB to the nucleus and promotes cell survival (Carter et al, 1996;Bhakar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%